Assessing shellfish harvesting and stakeholder perspectives on trade in Bangladesh’s largest wetland - Goutam Singha; M. Nazrul Islam; Shams M. Galib (Journal of Fisheries, 2025)
The trade of freshwater shellfish is growing but has received insufficient attention from researchers. In this study, we examined various aspects of shellfish harvesting (catch amount and composition, socio-economic profiles of shellfish collectors, distribution channels and perceptions of major stakeholder groups) over a six-month period (October 2023 to March 2024) in the largest wetland of Bangladesh, the Chalan Beel. The daily shellfish catch was higher during the low-water period (October – December; 10.7 ± 3.3 kg person–1) than during the dry period (January – March; 0.6 ± 0.2 kg person–1) (t-test: t = –32.4, p < 0.001). Catch composition varied significantly across groups (ANOVA: F = 10823, p < 0.001). Freshwater snails (primarily Pila globosa) contributed the most (70.1%) to the total catch, followed by mussels (primarily Lamellidens marginalis; 19.7%) and crab (Cancer pagurus; 10.2%). Three key actor groups involved in shellfish distribution were crab collectors, traders and consumers. Most collectors (65%), traders (54%) and consumers (89%) disagreed that shellfish are an important component of the aquatic environment. All traders and 96% of collectors agreed that shellfish collection and trade are profitable, whereas all consumers maintained a neutral standpoint. All consumers agreed that shellfish are good food, while the majority of collectors (93%) and traders (93%) remained neutral. Additionally, all consumers and most collectors (67%) and traders (73%) supported harvesting shellfish from other aquatic ecosystems. The results of this study are expected to be useful in formulating appropriate policies for wetland and resource management.